Эпистолярия как литературные беседы: Письма Г. В. Адамовича А. В. Бахраху [_Epistolaria_ as Literary Conversations: Letters of Georgy Adamovich to Alexander Bacherac] - Demidova, Olga (Slavica Revalensia, 2021)
This article is an attempt at close reading an extensive ego text (Georgy Adamovich’s letters to Alexander Bacherac of the 1940s – 1972) as a thirty-year-long literary conversation of two Russian émigré writers. Regarding the letters as a single cultural text, and relying on the hermeneutic and semiotic approaches, the article singles out three major layers of the text in question, and analyzes the textual body “inwardly,” i.e. starting from the purely existential-informational upper layer, proceeding to the layer of literary criticism, and finally reaching the layer of literary quotations and cultural allusions used as one of the basic devices forming Adamovich’s epistolary style. Comparing the letters with Adamovich’s famous Literary Conversations (Literaturnye besedy) of the 1920s, the author argues that in his correspondence with Bacherach Adamovich followed the tradition of the Russian friendly literary-philosophical discourse borrowed from the West in the 1800s and developed in the 1820s – 1830s by Alexander Pushkin and his circle.